Synthesis, Characterization and Pesticide Activities of Some Novel Tutin Derivatives - Cui, Jun; Li, Menglou (Asian Journal of Chemistry, 2013)
Seven novel tutin acylation derivatives (T1-T7) were synthesized to determine their pesticide activity against Mythimna separata. The structural assignments of these semisynthetic compounds were examined based on their IR, ESIMS and 1H- and 13C-NMR spectra data. Compared with tutin, those derivatives possessing potent anti-feedant activity and the most potent was 2-(3,5-dichlorobenzoyloxy)-tutin (T7).